"MICE Destinations Branding from Corporate Branding perspective". (31st May 2016) - Hoque, Mohammad Enamul
Abstract: The paper demonstrates that how branding and corporate branding approach has been utilized into destination branding, both tourist and MICE destination. The research addresses most common features in both MICE destination branding and corporate branding. An abductive approach of research was employed and the process was substantiated independently. The study detects and highlights that corporate branding issues may offer new intuitions in MICE destination branding. Consequently, the study suggests that corporate branding approach can be utilized for MICE destination branding. In addition, this provides new-fangled acumens for destination management organisation as well as for corporate branding researcher to conduct corporate branding research in different context.